Taxonomic and Functional Diversity of Rhizosphere Microbiome Recruited From Compost Synergistically Determined by Plant Species and Compost - Wang, Ning; Li, Huixiu; Wang, Bo; Ding, Jia; Liu, Yingjie; Wei, Yuquan; Li, Ji; Ding, Guo-Chun (Frontiers in Microbiology, 2022)
Compost is frequently served as the first reservoir for plants to recruit rhizosphere microbiome when used as growing substrate in the seedling nursery. In the present study, recruitment of rhizosphere microbiome from two composts by tomato, pepper, or maize was addressed by shotgun metagenomics and 16S rRNA amplicon sequencing. The 16S rRNA amplicon sequencing analysis showed that 41% of variation in the rhizosphere bacterial community was explained by compost, in contrast to 23% by plant species. Proteobacterial genera were commonly recruited by all three plant species with specific selections for Ralstonia by tomato and Enterobacteria by maize. These findings were confirmed mainly by analysis of 16S rRNA retrieved from the shotgun metagenomics library. Approximately 70% of functional gene clusters differed more than seven-fold in abundance between rhizosphere and compost. Functional groups associated with the sensing and up-taking of C3 and C4 carboxylic acids, amino acids, monosaccharide, production of antimicrobial substances, and antibiotic resistance were over-represented in the rhizosphere. In summary, compost and plant species synergistically shaped the composition of the rhizosphere microbiome and selected for functional traits associated with the competition on root exudates.